Creep crack energy dissipation and instability prediction in micritic bioclastic limestone - Mo, Zuguo; Qian, Li; Yao, Tianzhi; Gao, Yunpeng; Zhang, Ru; Liu, Enlong; Zhang, Jianhai (Frontiers in Earth Science, 2023)
Time-dependent deformation and long-term stability of rocks are important issues in water conservancy and geotechnical engineering. Currently, there are no well-accepted theoretical criteria to predict stability and damage with time-dependent deformation. In-depth research is still needed. Multilevel creep experiments were performed on micritic bioclastic limestone, obtained from a continuously deforming tunnel in Xinjiang, China. Based on crack strain theory, the axial crack strain evolution characteristics during loading and creep processes were investigated. The evolutionary characteristics of the crack dissipation energy density, which is obtained via integration of the crack strain during loading and creep, are revealed. The energy dissipation leading to rock fracture in each multilevel creep experiment is identified and used to calculate the total energy dissipated at the point at which the rock loses strength. A rock instability index based on the creep crack dissipation energy density is proposed. An instability index evolution model is proposed, expressed as a surface for the instability index evolution with the bearing state (Rd) and time. Based on the instability index surface, the stress threshold creep sensitive stresscs was defined. The time-dependent instability index surface was divided into a long-term stability zone (Z1), an initial time-dependent instability zone (Z2), a time-dependent instability stable evolution zone (Z3) and a time-dependent instability sensitive zone (Z4) by the initial crack stress, crack damage stress, and creep sensitive stress. The instability index model was established as an energy instability evolution criterion to evaluate and predict the rock instability and lifespan under specific stress states.